Model Pengelolaan Sampah Berbasis Komunitas di Apartemen Gateway Ahmad Yani Bandung - Sarah Asrina Rangkuti; Abdul Rahman; Septiana Dwi Putrianti; Muhammad Nur Afandi (Jurnal Ilmiah Global Education, 2026)
The problem of urban waste is an increasingly complex environmental issue along with increasing urbanization and the growth of vertical housing. Gateway Ahmad Yani Apartment, Bandung, as a densely populated residential area, faces serious problems related to waste accumulation, limited transportation capacity, and low resident participation in waste management. This study aims to analyze the currently implemented waste management system, identify obstacles and efforts that have been made, and formulate a sustainable community-based waste management model. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, field observations, documentation studies, and online surveys as supporting data. Data analysis was carried out using the Miles and Huberman model. The results show that waste management at Gateway Ahmad Yani Apartment, Bandung is still conventional, namely collection and disposal without sorting, thus causing various environmental and social problems. The main obstacles include low awareness of residents, limited sorting facilities, and weak implementation of sanctions. Therefore, this study formulates a community-based waste management model that emphasizes active resident participation, the application of the 3R principle (Reduce, Reuse, Recycle), a reward and sanction system, and collaboration between managers and the community. This model is expected to reduce waste generation, improve the quality of the residential environment, and support sustainable development.